2013
DOI: 10.15835/nbha4129339
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in the Forest Products Industry: The Malaysian Experience

Abstract: The forest products industry is an important socioeconomic sector to many developing countries, both in terms of foreign exchange earnings and employment. In the case of Malaysia, the industry has been one of the fastest growing manufacturing sectors in the country, driven primarily by comparative advantages derived from factor inputs. However, with increasing competition from other cheaper producing nations particularly China and Vietnam, the Malaysian forest products industry is forced to transform and move … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…From the 39 manufacturers initially identified, only 30 manufacturers consented to participate in the study. Three types of value-added wood products were chosen for this study, which included door, flooring, and furniture manufacturing industries, as these were among the fastest growing sub-sectors in the wood-based industry in the country and most of the manufacturing outfits were classified as large manufacturers (i.e., employing more than 100 workers and with an annual turnover in excess of US $12.5 million) (Ratnasingam et al 2013). …”
Section: Target Respondentsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the 39 manufacturers initially identified, only 30 manufacturers consented to participate in the study. Three types of value-added wood products were chosen for this study, which included door, flooring, and furniture manufacturing industries, as these were among the fastest growing sub-sectors in the wood-based industry in the country and most of the manufacturing outfits were classified as large manufacturers (i.e., employing more than 100 workers and with an annual turnover in excess of US $12.5 million) (Ratnasingam et al 2013). …”
Section: Target Respondentsmentioning
confidence: 99%
“…This is most likely due to the fact that value-added wood products are purchased on perceived value rather than the actual value (Ratnasingam et al 2013).…”
Section: Factor Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to Malaysia, far too little attention has been given to the productivity performance of the timber sector. Although a study by Ratnasingam et al (2013) on the extent of innovation in the Malaysian furniture industry had shown an indirect link to productivity growth, the literature available on this topic is scarce (Pang et al 2015). Against the background of a huge industry, contributing more than RM 22 billion in export earnings in 2015, and with almost 3,000 manufacturing establishments employing nearly 180,000 workers, the questions of what drives the industry's growth and the relative performance of the various timber sub-sectors has not been well researched.…”
Section: Introductionmentioning
confidence: 99%